Evaluation of scientific outputs of dentistry in Tehran university of medical sciences in ResearchGate and Mendeley networks using the Scopus citation database between 2015-2016 - Somayeh Azimi Kangarshahi; Seyed Javad Ghazi Mirsaeid; Zahra Ganjipour (Tehran University of Medical Sciences, 2019)
Background and Aims: The emergence of social web and impact on the communication of the individuals and the scientific activities of various communities has created serious research links among researchers. This issue that how Iranian researchers keep up to date themselves with new technologies and use them to engage in scientific issues has been a challenge that is constantly being addressed in the digital world. Therefore, the purpose of this study was to evaluate the scientific production of dentistry in Tehran University of Medical Sciences in the networks of ResearchGate and Mendeley using the Scopus citation database between 2015 and 2016. Materials and Methods: The study population included all scientific articles in the field of dentistry of Tehran University of Medical Sciences which were indexed in Scopus database between 2013-2016. The results were presented using descriptive statistics in the form of charts and tables. Results: In this study, it was determined that the scientific outputs of the researchers from Tehran University of Medical Sciences increased in 2015 and 2016. It was also found that the coverage of articles in the field of dentistry published by researchers at Tehran Medical Sciences Universities in the Scopus citation database in the mentioned years, were in a good position in both the Mendeley and ResearchGate networks. In addition, the number of references to the articles by researchers at Tehran University of Medical Sciences on the ResearchGate network in the field of dentistry was more than the Mendeley network. Conclusion: Based on the results of this study, it can be concluded that the performance of the researchers of the Tehran University of Medical Sciences in the field of oral and dental care and the extent of their coverage in the social networks of ResearchGate and Mendeley was high and desirable.